2013
DOI: 10.1615/critrevbiomedeng.2013008077
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the Microvasculature and Its Microenvironment

Abstract: The microvasculature is a dynamic cellular system necessary for tissue health and function. Therapeutic strategies that target the microvasculature are expanding and evolving, including those promoting angiogenesis and microvascular expansion. When considering how to manipulate angiogenesis, either as part of a tissue construction approach or a therapy to improve tissue blood flow, it is important to know the microenvironmental factors that regulate and direct neovessel sprouting and growth. Much is known conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 341 publications
(431 reference statements)
0
17
0
Order By: Relevance
“…As discussed above, different strategies have been pursued to promote blood perfusion in cardiac grafts, such as co-implantation of endothelial cells and/or addition of angiogenic factors [113][114][115][116][117][118]. Although these approaches can lead to the successful formation of vessels within implanted grafts, the drawback is that the time required for new vessels to form and start carrying blood [6,[119][120][121][122] is higher than the rate at which the death of A C C E P T E D M A N U S C R I P T…”
Section: Future Directions and Summarymentioning
confidence: 99%
“…As discussed above, different strategies have been pursued to promote blood perfusion in cardiac grafts, such as co-implantation of endothelial cells and/or addition of angiogenic factors [113][114][115][116][117][118]. Although these approaches can lead to the successful formation of vessels within implanted grafts, the drawback is that the time required for new vessels to form and start carrying blood [6,[119][120][121][122] is higher than the rate at which the death of A C C E P T E D M A N U S C R I P T…”
Section: Future Directions and Summarymentioning
confidence: 99%
“…Actually, around 20% of the patterned samples were scored with 3 vessels or more whereas the non-patterned membrane had very low score. Other studies have shown that surface topographies are able to influence cell behavior, however, the effect is dependent on the dimensions and the specific morphology of the surface topographies applied [ 49 , 69 ]. For example, Song et al showed that 10 μm micropost-textured PDMS scaffolds, combined with biochemical stimulus and MSCs, had a positive effect on vessel formation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…There, we coated the membrane lid with fibronectin but we did not use angiogenic gels since those could block the membrane pores limiting the transport properties of the implant. The distance between the patterns was 100 µm, since it has been shown that cell alignment occurs in patterns between 20–130 µm [ 49 ]. These results were in accordance with literature where it has been shown that HUVEC alignment can be tailored using micropatterns [ 50 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is this deformation (the direction and extent) and not directly acting stresses that influences the orientation of vessel elements such that they align perpendicular to the primary direction of compressive strain. Thus, in fabricating microvasculatures, the composition, shape, and physical constraints placed on the cell/tissue system can be manipulated to direct final vascular architectures [109].…”
Section: Tissue Stromal Mechanicsmentioning
confidence: 99%